Otimização da Ferramenta de Monitoramento Zabbix no Hospital Universitário de Santa Maria - Röpke, Vinícius; Guarienti, Matheus; Rizzetti, Tiago Antonio (Anais da Escola Regional de Redes de Computadores (ERRC); 2019: Anais da XVII Escola Regional de Redes de Computadores, 2019)
This article describes the optimization of the Zabbix network monitoring tool at the Hospital Universitário de Santa Maria, where existing servers had been presenting problems generated by the misconfiguration of the tool as a whole. The high amount of network assets monitored by the tool, and the abundance of data collected, slowed the machine, making it difficult to use when necessary. New network assets and locations to be added were analyzed to ensure item history. Thus it is possible to generate reports for statistics, and reduce the computational effort of the tool to bring real-time information of network problems. To solve the problems presented, and obtain concrete data of the environment, it was aimed to optimize the tool itself, reviewing items from each host on the machine, linking templates, adjusting the use of the housekeepinp function (acting to remove unused records in database level), among other processes to improve server performance. This facilitates the use of the tool.